2016
DOI: 10.3389/fpsyg.2016.01640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on the Dynamics of Reactive and Proactive Cognitive Control of Response Interference

Abstract: A prime-target interference task was used to investigate the effects of cognitive aging on reactive and proactive control after eliminating frequency confounds and feature repetitions from the cognitive control measures. We used distributional analyses to explore the dynamics of the two control functions by distinguishing the strength of incorrect response capture and the efficiency of suppression control. For reactive control, within-trial conflict control and between-trial conflict adaption were analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…While providing a cue during updating disentangles the removal, encoding, and attention reorientation confound, it can be argued that the results of and the present set of studies may also be interpreted in terms of individual differences in the general capacity for cue utilization. This hypothesis would assume that participants may differ primarily in their ability to use cues to anticipate task demands and prepare for updating rather than their efficiency to perform the actual removal operation itself (see, e.g., Brouwers, Wiggins, Helton, O'Hare, & Griffin, 2016;Xiang et al, 2016). While we acknowledge that individuals may differ in the effectiveness of their cue utilization, we argue against the notion that this cue-utilization hypothesis can explain present findings.…”
Section: Alternative Interpretations Regarding the Processing Involvementioning
confidence: 59%
“…While providing a cue during updating disentangles the removal, encoding, and attention reorientation confound, it can be argued that the results of and the present set of studies may also be interpreted in terms of individual differences in the general capacity for cue utilization. This hypothesis would assume that participants may differ primarily in their ability to use cues to anticipate task demands and prepare for updating rather than their efficiency to perform the actual removal operation itself (see, e.g., Brouwers, Wiggins, Helton, O'Hare, & Griffin, 2016;Xiang et al, 2016). While we acknowledge that individuals may differ in the effectiveness of their cue utilization, we argue against the notion that this cue-utilization hypothesis can explain present findings.…”
Section: Alternative Interpretations Regarding the Processing Involvementioning
confidence: 59%
“…The age-related decline was observed in alternation trials disregarding prior sequence characteristics, suggesting that age only affected just-in-time selection. The reactive control, but not proactive control, declined with aging (Xiang et al, 2016). That challenged earlier views of age can only affect proactive control (Botvinick et al, 2001;Braver & West, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies reported that old adults had selective difficulty in memorizing content-context associations but not in isolated contents (Artuso et al, 2017;Artuso & Palladino, 2011;McCormick-Huhn et al, 2018;Old & Naveh-Benjamin, 2008;Pelegrina et al, 2012) and the delays in selection were longer with a function of memory load (Artuso et al, 2017), implying that proactive control was impaired with aging. But Xiang et al (2016) reported that older adults had selective deficits in reactive control.…”
Section: Introductionmentioning
confidence: 99%
“…Another ERP study on different tasks (stimulus-response compatibility, Simon task and a hybrid choice-reaction/No-Go task) found differences in the magnitude of the Gratton effect between children and young adults (Smulders et al, 2018), which disappeared after correction of processing speed differences among the age-groups. Results on aging (Puccioni and Vallesi, 2012; Aisenberg et al, 2014; Aschenbrenner and Balota, 2015; Xiang et al, 2016), suggest that the Gratton effect is preserved. This paradigm helped clarify two main hypotheses regarding decrease in cognitive performances with aging (Puccioni and Vallesi, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Regarding the SCE evolution across the lifespan, we are not aware of any study investigating how age impacts this effect all along the lifespan spectrum. There are, however, investigations on the transition from childhood to adulthood (Waxer and Morton, 2011; Kray et al, 2012; Larson et al, 2012; Ambrosi et al, 2016; Smulders et al, 2018) and on the transition from young to older adults (Puccioni and Vallesi, 2012; Aisenberg et al, 2014; Aschenbrenner and Balota, 2015; Xiang et al, 2016). These studies suggest that children show stronger interference effects and higher error rates relative to young adults, but when combining studies from the entire lifespan spectrum, the SCE seems globally stable across development, nonetheless showing stronger magnitudes at the extremities of the lifespan continuum.…”
Section: Introductionmentioning
confidence: 99%